Adaptive Parameter Estimation for an Energy Model of Belt Conveyor with DC Motor. Issue 4 (6th September 2013) - Shen, Yanjun; Xia, Xiaohua
ABSTRACT In practice, design parameters of a belt conveyor likely drift away from their design values by maintenance, readjustment, retrofit, abrasion, and circumstance change. For the purpose of energy optimization, these parameters should be estimated through experiments. In this paper, a new energy model of a DC motor driven belt conveyor is presented. Then, based on an adaptive observer, a parameter estimation algorithm is derived. In addition, under a persistent excitation condition, the convergence of the parameters to the desired values can also be concluded. Compared with the existing methods, our methods can be implemented by measuring only the feed rate of the belt conveyor and the angular velocity of the rotor of the DC motor.